The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1139/y73-048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Steroids on the Hepatic Glucuronidation and Biliary Excretion of Bilirubin

Abstract: In rats, treatment with spironolactone or pregnenolone-16α-carbonitrile (PCN) accelerates bile flow and enhances hepatic microsomal bilirubin–UDP glucuronyltransferase activity (EC 2.4.1.17) and the biliary transport maximum (Tm) of bilirubin. The distribution of ethylanthranilate azo-pigments in fractions separated by thin-layer chromatography also indicates increased glucuronidation of bilirubin. These findings explain the mechanism of enhanced serum bilirubin disappearance in rats treated with the steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
1

Year Published

1978
1978
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…In addition, PCN induces Z protein and, as an associated change, it increases the capacity of the liver to take up and store bilirubin and BSP. These findings are in total agreement with earlier investigations (17,18) in which it was shown that PCN enhances serum bilirubin clearance in rats.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In addition, PCN induces Z protein and, as an associated change, it increases the capacity of the liver to take up and store bilirubin and BSP. These findings are in total agreement with earlier investigations (17,18) in which it was shown that PCN enhances serum bilirubin clearance in rats.…”
Section: Discussionsupporting
confidence: 94%
“…Like phénobarbital, certain microsomal enzyme inducers -for instance, pregnenolone16a-carbonitrile (PCN) and spironolactonehave been shown to accelerate the clearance of bilirubin from serum (17), stimulate bile flow and increase hepatic microsomal bilirubin-UDP glucuronyltransferase activity as well as die biliary Tm of bilirubin (2,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different steroids might be involved or other hormones might be required to allow an effect of estrogens and progestogens to become manifest, thus exerting a permissing effect. It has also been proposed that alterations of drug-metabolizing enzymes during pregnancy is a consequence of a shift of hepatic progesterone metabolism from the hydroxylation pathway, producing inducers of microsomal enzymes such as pregnenolone 16a-carbonitrile, to the reduction pathway, producing inhibitors of microsomal enzymes such as pregnanediol (29). This hypothesis could also explain the present results, since pregnenolone-16a-carbonitrile was found to induce hepatic bilirubin conjugation (29) while pregnanendiol was found to inhibit it (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, PCN increases bile flow as well as the glucuronidation of bilirubin and clearance of sulphobromophthelein (BSP) (Zsigmond & Solymoss, 1972;Solymoss & Zsigmond, 1973). It also counters toxic effects of many substances in the rat (Selye, 1971).…”
mentioning
confidence: 99%